2007
DOI: 10.1016/j.phrs.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid system involvement in brain reward processes related to drug abuse

Abstract: Cannabis is the most commonly abused illegal drug in the world and its main psychoactive ingredient, delta-9-tetrahydrocannabinol (THC), produces rewarding effects in humans and non-human primates. Over the last several decades, an endogenous system comprised of cannabinoid receptors, endogenous ligands for these receptors and enzymes responsible for the synthesis and degradation of these endogenous cannabinoid ligands has been discovered and partly characterized. Experimental findings strongly suggest a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 189 publications
2
71
1
2
Order By: Relevance
“…Limited drug-like responding in tests with D-amphetamine and morphine also occurred in rats trained with lower (1.8 mg/kg) and higher (5.6 mg/kg) doses of Δ 9 -THC, as well as in rats trained with 10 mg/kg mAEA (Järbe et al 1998a(Järbe et al , 2006). Yet, mAEA has been reported to augment methamphetamine self-administration in rodents (Vinklerová et al 2002), and in common with other drugs of abuse, CB 1 R agonists have been shown to result in increased dopamine levels in the nucleus accumbens (discussed in Solinas et al 2007b). Although speculative, such commonality in end result might have been a contributing factor for the relatively high degree of drug-like responding observed with Damphetamine in the rats discriminating between 3 mg/kg AM1346 and vehicle.…”
Section: Discussionmentioning
confidence: 98%
“…Limited drug-like responding in tests with D-amphetamine and morphine also occurred in rats trained with lower (1.8 mg/kg) and higher (5.6 mg/kg) doses of Δ 9 -THC, as well as in rats trained with 10 mg/kg mAEA (Järbe et al 1998a(Järbe et al , 2006). Yet, mAEA has been reported to augment methamphetamine self-administration in rodents (Vinklerová et al 2002), and in common with other drugs of abuse, CB 1 R agonists have been shown to result in increased dopamine levels in the nucleus accumbens (discussed in Solinas et al 2007b). Although speculative, such commonality in end result might have been a contributing factor for the relatively high degree of drug-like responding observed with Damphetamine in the rats discriminating between 3 mg/kg AM1346 and vehicle.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, inhibition of the fatty acid amide (FAAH) by URB597, but not inhibition of AEA transport by AM404 or UCM707, considerably potentiates both the duration and the magnitude of the AEA-induced DA rise, suggesting brain specificity for FAAH versus transport/FAAH inactivation of AEA (Solinas et al, 2006(Solinas et al, , 2007b.…”
Section: Neurochemical Evidencementioning
confidence: 98%
“…More recently, it has been reported that AEA also possesses the ability to produce a fast and significant elevation in extracellular DA levels in the shell of the NAc when injected intravenously (Solinas et al, 2006(Solinas et al, , 2007b. In addition, inhibition of the fatty acid amide (FAAH) by URB597, but not inhibition of AEA transport by AM404 or UCM707, considerably potentiates both the duration and the magnitude of the AEA-induced DA rise, suggesting brain specificity for FAAH versus transport/FAAH inactivation of AEA (Solinas et al, 2006(Solinas et al, , 2007b.…”
Section: Neurochemical Evidencementioning
confidence: 99%
“…Isso significa que o resultado final será dependente do set (contexto interior) e setting (contexto ambiental) (Figura 3). Dessa forma, pode-se entender as diferentes consequências associadas ao uso terapêutico ou hedonístico da Cannabis, incluindo a transição (ou não) de uso experimental para hedonístico e os diferentes padrões de uso recreacional 71 . A modulação dopaminérgica do eixo ATV-FPM-NAc no NAc ocorre de forma bastante similar, podendo ocorrer modulação direta e indireta 40,67,69,70 .…”
Section: Sistema Endocanabinoide E Circuito Do Prazerunclassified